Youth Baseball and Data Analytics: Quantifying Risk Management and Producing Neoliberal Responsible Citizenship Through the GameChanger App. (February 2020) - Sanderson, Jimmy; Baerg, Andrew
Data analytics have become a significant evaluation mechanism within professional baseball to objectively quantify performance. This trend also has integrated into youth baseball through statistical applications that digitally capture and evaluate player performance. This essay examines the influence of baseball stat-tracking app GameChanger in the context of Little League Baseball and how it positions players, parents, and coaches to understand responsible citizenship through neoliberal risk management. The essay considers how risk management quantification and its accompanying development of responsible citizenship through GameChanger impact each of these stakeholder groups. As statistical evaluation becomes more commonplace in Little League Baseball, it shifts the Little League Experience into a more quantified, risk-management enterprise. In doing so, the experience becomes altered by enhancing opportunities for those players whom data suggest possess the maximum utility for production.